FORMULATION AND EVALUATION OF AMOXICILLIN TRIHYDRATE FAST DISINTEGRATING TABLET (FDT) USING SODIUM STARCH GLYCOLATE (SSG) AS SUPER DISINTEGRANT - Widjaja, Tiyon; Hasna Nabila, Annisa; Qaanita, Nasya (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2024)
This study was conducted to make a fast-disintegrating amoxicillin tablet formulation using a super disintegrant. Fast disintegrating tablets are tablets that quickly disintegrate after being placed in the mouth so that they can provide benefits for patients who have difficulty getting water or patients who have difficulty swallowing tablet drugs. Amoxicillin fast disintegrating tablet uses lactose monohydrate as filler, avicel pH 102 as binder, sodium starch glycolate as super disintegrant, stearic acid as lubricant, and aspartame as sweetener. The results of the granule evaluation showed that the fines produced from the particle distribution test were 4,56%. The tablet evaluation results showed that the tablets produced had a diameter of 0.6 0,0 cm with a thickness of 0,4 0,0 cm. The average weight of the tablets produced was 143,62 3,04 mg. The hardness of the tablets obtained was 3,962 ± 0,5678 kg with an average tablet friability of 0,63 ± 0,0028%. Tablet dissolution results showed that within 30 minutes tablet 1 dissolved as much as 116,21% and tablet 2 dissolved as much as 116,38%. The results of the disintegration time test showed that the tablets disintegrated for 44,44 ± 15,3957 seconds and the wetting time test was pored for 20 seconds. All evaluations carried out have met the predetermined acceptance requirements. Therefore, this FDT amoxicillin preparation formulation is declared as an optimal and effective formulation for use.